Structure-Based and Molecular Modeling Studies for the Discovery of Cyclic Imides as Reversible Cruzain Inhibitors With Potent Anti-Trypanosoma cruzi Activity - Ferreira, Rafael A. A.; Pauli, Ivani; Sampaio, Thiago S.; de Souza, Mariana L.; Ferreira, Leonardo L. G.; Magalhães, Luma G.; Rezende, Celso de O.; Ferreira, Rafaela S.; Krogh, Renata; Dias, Luiz C.; Andricopulo, Adriano D. (Frontiers in Chemistry, 2019)
Chagas disease causes approximately 10,000 deaths each year, mainly in Latin America, where it is endemic. The currently available chemotherapeutic agents are ineffective in the chronic stage of the disease, and the lack of pharmaceutical innovation for Chagas disease highlights the urgent need for the development of new drugs. The enzyme cruzain, the main cysteine protease of Trypanosoma cruzi, has been explored as a validated molecular target for drug discovery. Herein, the design, molecular modeling studies, synthesis, and biological evaluation of cyclic imides as cruzain inhibitors are described. Starting with a micromolar-range cruzain inhibitor (3a, IC50 = 2.2 µM), this molecular optimization strategy resulted in the nanomolar-range inhibitor 10j (IC50 = 0.6 µM), which is highly active against T. cruzi intracellular amastigotes (IC50 = 1.0 µM). Moreover, most compounds were selective towards T. cruzi over human fibroblasts, which were used as host cells, and are less toxic to hepatic cells than the marketed drug benznidazole. This study enabled the discovery of novel chemical diversity and established robust structure-activity relationships to guide the design of optimized cruzain inhibitors as new trypanocidal agents.